2021
DOI: 10.1097/rhu.0000000000001299
|View full text |Cite
|
Sign up to set email alerts
|

Parental Smoking Influence in Disease Activity in a Low-Income Juvenile Idiopathic Arthritis Cohort

Abstract: Data represent n (%). Patients with JIA or healthy controls (control) were evaluated for parental smoking using minimally adjusted general linear models with robust errors estimators (adjusted for age, sex, disease category, parental education, family monthly income).CI indicates confidence interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
5
1
Order By: Relevance
“…Previous studies have reported a lower prevalence of smokers in Brazil as compared with European countries, which was reproduced in the present study. Be as it may, our data showed no difference in CBP or IBP regardless of smoking habit 10,23 …”
Section: Discussioncontrasting
confidence: 45%
See 4 more Smart Citations
“…Previous studies have reported a lower prevalence of smokers in Brazil as compared with European countries, which was reproduced in the present study. Be as it may, our data showed no difference in CBP or IBP regardless of smoking habit 10,23 …”
Section: Discussioncontrasting
confidence: 45%
“…This specific item has been previously considered as unable to differentiate IBP from no IBP in patients reporting CBP 8 . The fact that CBP was highly prevalent in our sample, which was probably associated with a majority declaring blue-collar jobs, 10 might have influenced this result. Using ASAS questionnaire, we also observed a significantly higher prevalence of IBP in women.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations